Factors Influencing the Adoption of Climate-Smart Agriculture among Maize and Sorghum Farmers in Northern Ghana. (International Journal of Agricultural Extension and Education, 2025)
This study investigates the determinants of climate-smart agricultural practice adoption among smallholder maize and sorghum farmers in Northern Ghana, which is crucial for enhancing crop productivity and ensuring regional food security. By analysing data from 1,000 smallholder farmers through descriptive statistics, a transdisciplinary approach and a multivariate probit regression model, the study reveals a concerning overreliance on chemical fertilisers, constituting 56% overall adoption, 72% in the Northern Region and 51% in the Upper West. Contrary, conservation agriculture emerges as a promising practice, with a 56% adoption rate in the Upper East. Factors that determine the adoption include; farmer demographics, land tenure system, access to climate information, market availability, presence of agriculture extension officers, and geographical location. These findings underscore the urgent need for government investment in research, capacity building, and infrastructure in Northern Ghana to foster broader adoption of sustainable practices. This study offers significant insights into the dynamics of climate-smart agricultural adoption in the region, with implications for agricultural sustainability and food security.
Keywords: agriculture productivity; climate change; food security; adoption; mitigation; sustainable agriculture; smallholder farming